Effect of an α-Tocopherol-Containing Antioxidant Parenteral Emulsion upon Gut Microbiota in Preterm Infants - Arboleya, Silvia; Reyes-Gavilán, Clara G. de los; Konstantinou, Dimitris; Skouroliakou, Maria; Gueimonde, Miguel (International Journal of Child Health and Nutrition, 2015)
Preterm babies are born with an immature intestine and are at higher risk for intestinal failure and needing for parenteral nutrition than full-term newborns. These babies show an altered intestinal microbiota, which may results of key importance for later health. However, there is a lack of information on effect of parenteral formulas upon the establishing infant microbiota. Moreover, the microbiota alterations present in preterm newborns have been related with an altered redox-potential which hinders the establishment of strict anaerobes. Thus, interventions aimed at reducing the oxidative stress in these infants, including those under parenteral nutrition, could also affect the intestinal microbiota composition. We assessed the effect upon the gut microbiota of the administration during 30 days of a lipid emulsion, containing ω3 polyunsaturated fatty acids and α-tocopherol, or a control emulsion containing soybean-bases lipids to parenterally-fed preterm newborns. In spite of its high antioxidant potential, the infants receiving the experimental fat emulsion showed a trend to increase of facultative anaerobes such as enterobacteria and specifically of Klebsiella. This study stresses the need of further work monitoring the impact of early-life parenteral nutrition on the establishment of the intestinal microbiota.